Primary Adenoid Cystic Carcinoma of the Upper Anterior Mediastinum Mimicking a Thyroid Tumor: A Case Report and Review of Literature - Wu, Qiuji; Sun, Weizi; Bu, Jiajun; Xiang, Yuanhang; Zhong, Yahua (Frontiers in Endocrinology, 2020)
Primary adenoid cystic carcinoma of the upper anterior mediastinum mimicking thyroid tumor was rarely seen in clinical practice and lacked standard treatment. Here we reported a 47-year old female patient with adenoid cystic carcinoma originated from the upper anterior mediastinum presented as a thyroid gland tumor. The patient received surgical resection of the gross tumor and underwent post-surgical chemotherapy and radiotherapy. The patient was free from local recurrence three years following initial treatment, but developed multiple lung metastases. She remained observation without discomfort and was still under follow-up. We also summarized recent report on similar cases and hope to provide some experience for future clinical practice.